Comparison of Students' Mathematical Concept Understanding Ability in Polyhedron Material Using the Discovery Learning and Core Learning Model with The Assistance of Pop-Up Book Media - Inanda Shofa Azahroh; Fitria Zana Kumala (Jurnal Pendidikan Matematika (JPM), 2024)
This research was motivated by the low ability of class VIII students at MTs N 1 Purbalingga to understand mathematical concepts. This research aims to compare students' ability to understand mathematical concepts in flat-sided geometric material using two different learning models, namely discovery learning and Connecting, Organizing, Reflecting, And Extending (CORE) with the help of pop-up book media. The research method used is quantitative with a quasi-experimental type of research. The population in this study were class VIII students at MTs N 1 Purbalingga for the 2022/2023 academic year. The sampling technique used simple random sampling, and the sample in this study were students in classes VIII D and VIII E, totaling 76 students. In experimental class I, I received teaching using the discovery learning model assisted by pop-up books. For experimental class II, I received teaching using the CORE model assisted by pop-up books. The data collection method uses tests in the form of pretest and posttest. The data analysis technique uses the n-gain and two independent samples t-tests. The research results showed that the average n-gain score in experimental class I was 0.656; in experimental class II, it was 0.366, which was in the medium category. Judging from the n-gain interpretation, the average percentage value obtained by experimental class I, namely 65.5%, is interpreted as quite effective. It is interpreted as ineffective in experimental class II, namely 36.6%. Based on analysis using the t-test for two independent samples, the significance value was 0.000 < α=0.05, so it can be concluded that there is a significant difference between the ability to understand mathematical concepts of students who use the pop-up book-assisted discovery learning model and the CORE assisted learning model on flat-sided building materials.